Steel wire ropes failure analysis: Experimental study. (September 2018) - Mouradi, Houda; El Barkany, Abdellah; El Biyaali, Ahmed
Abstract: Steel wire ropes are structural elements which occupy central functions in the industrial, maritime and civil engineering domain. They consist of several steel wires twisted together to make a structure with huge mechanical properties combining axial strength and stiffness with bending flexibility. In the great majority of applications, steel wire ropes are subjected to several mechanisms of damage. These mechanisms can lead to the premature break of the rope components causing its sudden and unexpected failure. In this context, the aim of this paper is to characterize the mechanical behavior of the wire rope in service along with monitoring the evolution of its damage in order to facilitate the determination of the conditions of use reliably. For this, an experimental study was presented in order to trace the evolution of the non-rotating rope 19 × 7 damage and to define its different stages as well as the critical fraction of life which can lead to sudden failure of this wire rope. The adopted approach is proactive and facilitates the prediction of the rope failure based solely on static tests and without doing any dynamic tests. Indeed, this approach is based on the application of two models of damage: The static damage which consists in tracking the evolution of the residual ultimate forces taken at different percentages of the life of the test specimen. The second model of damage is that which is based on the reduction of the strength and the endurance limit of damaged wire rope according to the unified theory. This technique is highly desirable in the industrial field so as to establish a rigorous maintenance system as well as to ensure the ability to work in a safe reliable environment. Highlights: Monitoring the loss of the wire rope's strength at different percentage of its degradation. Identifying the stages of the rope's damage in service and the critical fraction of life which can lead to its sudden failure. Tracking the damage of the wire rope according to its different fraction of life for various loading levels. Illustration of the decrease in both the residual ultimate force and the endurance limit of the damaged wire ropes. The Miner rule overestimates the damage since the damage curves tend gradually towards linearity (Miner rule) for higher loadings.